Midwife Virtual Menggunakan Aplikasi Pelayanan Chatbot Polita Sebagai Media Untuk Informasi Imunisasi - Novi Aryani Fitri,; Ismaulidia Nurvembrianty, (SATIN - Sains dan Teknologi Informasi, 2021)
There is still a lack of education regarding the importance of immunizing children. Some parents still think that vaccines are haram and vaccines can cause children to become disabled or die. Especially during the Covid-19 pandemic, parents are still worried about whether their children should be immunized or not. Based on the problems described, an autoresponder application was created to be able to educate parents about the benefits of the immunization program. The platform used in the chatbot application is Telegram using the cosine similarity method and using the Tf-IDF method to calculate the weight of each commonly used word. This study uses the aiogram library and implements the NLP program in Python. From the test results of the chatbot application, it is stated that the precision value is 77%, the accuracy is 63%, and the recall is 74%, this shows that the higher the recall value and precision, the better the performance of the proposed system, it can be said that this chatbot fulfills the objectives provide education to parents about the implementation of immunization during the Covid-19 pandemic.